Determination of age-dependent endogenous indole-3 acetic acid (IAA) level in different organs of tomato plants - Tasnim Ahmed; Rafiza Islam; Nargis Parvin; Mohammad Shoeb (Current Research on Bioscences and Biotechnology, 2022)
Indole-3-acetic acid (IAA), a phytohormone, is a crucial modulator of plant growth and development. As increased levels of endogenous IAA is responsible for inhibitory effects on plants, knowing its concentration would be helpful for controlling exogenous IAA input. An optimum endogenous IAA level is required for proper growth and development of plant with good health status. Hence, in this study, we have detected and measured IAA present in tomato root, shoot, leaves and fruits at two different ages (25 days and 50 days) by Reversed-Phase High Performance Liquid Chromatography (RP-HPLC), a suitable chromatographic method for separating molecules based on hydrophobicity. We observed that the endogenous level of IAA was significantly higher in roots, shoots, leaves and fruits at 50-days old plant compared to 25-days old mature plant (p-value <0.01). These results suggested that the IAA level may increase with the increase of the age of tomato plants. The tomato plants showed good vigor with IAA range 0.3-3.0 µg/g.F.W (25 days) and 3.4-7.5 µg/g.F.W (50 days) of age, respectively, implying that IAA might be used as a possible plant health indicator. Further study is needed to manipulate the IAA concentration for adequate plant growth and development.